(untitled) (Research, Society and Development, 2023)
Primary breast lymphoma (PBL) is a rare but distinct subtype of extranodal lymphoma, comprising 0.5% of breast malignancies, approximately 1% of all non-Hodgkin’s lymphomas (NHL) and <3% of extranodal lymphomas. Because the cases are rare, the diagnosis is difficult to establish by routine histopathological examination alone. This paper reports a case of a 53-year-old woman, complaining of a lump in the left breast. The lump is said to have been noticed since approximately 2 years ago on the nipple. The patient said that initially the lump was the size of a grape and then realized that it had enlarged since 3 weeks ago with a more chewy texture. Ultrasound of the left mammary, heterogeneous solid lesion with indistinct borders with dilatation of the drawerous duct with the appearance of intraductal calcification filling the superolateral and superomedial quadrants of the left mammary suggestively malignant (BIRADS 5). The microscopic appearance of the FNAB suggested a malignant round cell tumor. Based on the results of the biopsy and immunohistochemical examination, the results were positive CD 45, CD 20 positive, CD 3 negative, and Ki67 positive in 90% of tumor cell nuclei. It was concluded that it was a non-Hodgkin’s lymphoma, with a large diffuse pattern. The patient was reported did not survive.